Influence of supplementation of vitamin E on amelioration of ochratoxicosis in broiler chickens - SINGH, MOHIT; SINGH, RAM; MANDAL, A B (The Indian Journal of Animal Sciences, 2019)
In the present study, the effect of vitamin E supplementation in ochratoxin A (OTA) contaminated diet in amelioration of ochratoxicosis in broiler chickens was investigated. Day-old broiler chicks (n=240) were divided into six treatment groups (T1-control (basal diet); T2–T1 + 200 ppb OTA; T3–T1 + 100 mg vitamin E; T4–T1 + 200 mg vitamin E; T5–T2 + 100 mg vitamin E and T6–T2 + 200 mg vitamin E). Each diet was fed to 5 replicated groups of 8 birds each from 0 to 42 days of age. During overall growth period (0–6 week of age), the body weight gain (BWG) in ochratoxin contaminated diet (T2) fed group was lower than that of control. The BWG in group T5 was statistically similar to that of T2 fed diet and lower than that of control (T1). However, BWG in group T6 (200 mg vitamin E/kg) was higher than T2 and statistically similar to that of control group. Ochratoxin contamination in diet caused significant reduction in feed consumption, feed efficiency and livability percentage in broiler chickens. Addition of vitamin E (200 mg/kg) to the ochratoxin contaminated diet ameliorated the adverse effects on feed intake, FCR and livability percentage. Supplementation of vitamin E (200 mg/kg) to the ochratoxin contaminated diet also resulted in significant improvement in the relative weight of liver and bursa. It was concluded that experimentally induced ochratoxicosis with 200 ppb ochratoxin resulted in reduced production performance, enlargement of liver and regression of bursa. Addition of vitamin E (200 mg/kg) to the ochratoxin contaminated diet improved the production performance and relative weight of liver and bursa during 0–6 weeks of age of broiler chickens in experimentally induced ochratoxicosis caused by 200 ppb of dietary ochratoxin.